2018
DOI: 10.1007/s12602-018-9429-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Probiotic Lactobacillus fermentum MTCC: 5898-Fermented Milk Attenuates Dyslipidemia, Oxidative Stress, and Inflammation in Male Rats Fed on Cholesterol-Enriched Diet

Abstract: There is a growing and alarming prevalence that increased serum cholesterol is closely related to increased cardiovascular disease risk. Probiotic consumption could be a safe and natural strategy to combat. Therefore, we sought to examine the cholesterol-lowering potential of co-supplementation of probiotic bacteria Lactobacillus fermentum MTCC: 5898-fermented buffalo milk (2.5% fat) in rats fed cholesterol-enriched diet. Male Wistar rats were divided into three groups on the basis of feed, viz. group 1, fed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 36 publications
1
25
0
2
Order By: Relevance
“…Yadav et al [ 29 ] reported that the consumption of probiotic L. fermentum MTCC: 5898-fermented milk not only attenuated dyslipidemia, but also reduced oxidative stress and inflammation in male rats fed a cholesterol-enriched diet. Oxidative stress was measured by the activity of various anti-oxidative enzymes, such as catalase, superoxide dismutase and glutathione peroxidase, and the level of thiobarbituric acid reactive substances (TBARS) in the liver and kidney—a marker of lipid peroxidation.…”
Section: Probioticsmentioning
confidence: 99%
“…Yadav et al [ 29 ] reported that the consumption of probiotic L. fermentum MTCC: 5898-fermented milk not only attenuated dyslipidemia, but also reduced oxidative stress and inflammation in male rats fed a cholesterol-enriched diet. Oxidative stress was measured by the activity of various anti-oxidative enzymes, such as catalase, superoxide dismutase and glutathione peroxidase, and the level of thiobarbituric acid reactive substances (TBARS) in the liver and kidney—a marker of lipid peroxidation.…”
Section: Probioticsmentioning
confidence: 99%
“…The elucidation of differences in the mechanisms of action of T1D in humans and animals will facilitate experimental research and aid in discovering novel therapeutic strategies to ameliorate the T1D. Some of the most common animal models used to study the effect of probiotics, prebiotics and drugs on T1D are NOD mice [61], Streptozotocin (STZ)-induced T1D rats and mice [62,63], Alloxan-induced T1D Swiss Webster mice [64], BBDR rats [65,66], and Bio-Breeding Diabetic Pathogen (BBDP) rats [65,66]. The interactions of probiotics and prebiotics with gut microbiota and immune system and their involvement in T1D pathology are discussed separately for human and animal models.…”
Section: Role Of the Gut Microbiota-immune Axis In T1dmentioning
confidence: 99%
“…This was associated with decreased TNF-α and IL-6 levels but with no significant difference in the amount of TGF-β between control and treated rats [83]. The consumption of probiotic-fermented milk also helped in decreasing blood glucose levels, inflammation, oxidative stress and rate of gluconeogenesis [63,83]. Another study using diabetic rats concluded that the supplementation of probiotic strain L. plantarum appreciably reduced serum α-amylase action, favoring the glycemic index mechanism by restricting carbohydrate absorption and hydrolysis [84].…”
Section: Probiotic Interventions To Ameliorate T1dmentioning
confidence: 99%
“…Le TNF-α dérive principalement du tissu adipeux et contribue au dysfonctionnement endothélial et à la résistance à l'insuline, aussi bien, chez l'Homme que chez le rat [43,44]. Les mécanismes d'action du TNF-α ne sont pas encore bien élucidés mais il a été suggéré une diminution de l'ARNm de GLUT4 et une réduction du récepteur IRS (Insulin Receptor Substrate) [45]. Notre étude a bien mis en évidence, l'effet négatif de l'hypercholestérolémie, du diabète ainsi que leur association sur le statut inflammatoire, chez les rats puisqu'une augmentation des teneurs circulantes en CRP, TNF-α, IL-1β, IL-6 et en homocystéine, a été notée.…”
Section: Tnf- Homocystéine Et Protéine C-réactive (Crp)unclassified